Five-Level MLI-Based Grid-Connected Photovoltaic Systems: A Review on Control Methodologies, Modulation Strategies and Recent Developments - Anurag Tiwari; Vinayak Kumar; Ruchi Agarwal; Mohammad Amir; Mohammed A. Alharbi; S. M. Muyeen (IEEE Open Journal of Power Electronics)
This study provides an extensive overview of recent developments in grid-connected photovoltaic (PV) systems based on five-level Multilevel Inverters (MLIs), with an emphasis on modulation schemes, control approaches, and system architectures. Five-level MLI-based PV systems have become a crucial option as the relevance of renewable energy keeps increasing because of their increased efficiency, less harmonic distortion, and greater power quality. The study looks at several different control strategies, including grid synchronization approaches and Maximum Power Point Tracking (MPPT), to improve PV system performance and grid interaction. Several modulation techniques are also examined, with a focus on how they might lower harmonics and boost system performance. Examples of these techniques include pulse width modulation (PWM) and selective harmonic elimination (SHE). Further analysis of the structural features of five-level MLI-based systems is done, which helps to clarify the trade-offs between complexity, dependability, and cost. This analysis includes component needs and scalability concerns. Researchers and engineers working on the design, control, and deployment of sophisticated MLI-based PV systems in grid-connected applications may learn from this paper.